2021
DOI: 10.1371/journal.pone.0258191
|View full text |Cite
|
Sign up to set email alerts
|

The protective performance of reusable cloth face masks, disposable procedure masks, KN95 masks and N95 respirators: Filtration and total inward leakage

Abstract: Face coverings are a key component of preventive health measure strategies to mitigate the spread of respiratory illnesses. In this study five groups of masks were investigated that are of particular relevance to the SARS-CoV-2 pandemic: re-usable, fabric two-layer and multi-layer masks, disposable procedure/surgical masks, KN95 and N95 filtering facepiece respirators. Experimental work focussed on the particle penetration through mask materials as a function of particle diameter, and the total inward leakage … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 82 publications
4
27
0
3
Order By: Relevance
“…In agreement with that observation, the results of the present study indicated that mask breathability has a major consistent effect on leak performance, as masks with high breathability showed markedly less leakage. This is also in agreement with that recently reported by Duncan et al, suggesting that a high pressure drop may be partially responsible for mask leakage at least during exhalation [ 44 ]. Our work not only confirmed this hypothesis, but evidenced that high breathability can drastically limit the mask leakage, facilitating the passage of the airflow through the mask filter also when the face fit is not optimized.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with that observation, the results of the present study indicated that mask breathability has a major consistent effect on leak performance, as masks with high breathability showed markedly less leakage. This is also in agreement with that recently reported by Duncan et al, suggesting that a high pressure drop may be partially responsible for mask leakage at least during exhalation [ 44 ]. Our work not only confirmed this hypothesis, but evidenced that high breathability can drastically limit the mask leakage, facilitating the passage of the airflow through the mask filter also when the face fit is not optimized.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, the fraction of air leaking from the face seal plays a key role in the overall filtration efficiency and has an impact also on the whole mask breathability. In their recent work, Duncan and co-workers demonstrated the importance of the inward leakage in the protection efficiency of a mask and how this is influenced by the mask fit [ 44 ]. In the present study we measured the outward leakage on some typical community and surgical masks, providing a simple method for a quantitative estimation of the flow repartition at realistic flow rates.…”
Section: Discussionmentioning
confidence: 99%
“…La línea negra suaviza los puntos (FFT). La línea verde continua es el ajuste monoexponencial de la data experimental, la emisión de la lámpara UVC alcanza un valor máximo de 25 mW luego de 400 s. Potencia mínima emitida ∼8 mW La eficiencia de la esterilización también depende de la regularidad y el área expuesta en la superficie del material, ya que existe una dosis mínima de radiación UVC para desactivar los microorganismos [20,21], [28,29]. Por lo tanto, una esterilización exitosa ocurrirá solamente si toda la superficie del material está expuesta a la radiación UVC, porque cualquier sombra producida por las capas de tela de las máscaras puede reducir la efectividad de la esterilización.…”
Section: Medidas Fotométricasunclassified
“…La dosis entre 0,5 y 1,8 J/cm 2 fue capaz de desactivar 99,9 % de los patógenos, tales como algunos tipos de Influenza A, MERS-CoV, SARS-CoV y el bacteriófago MS2. La capacidad de filtrado de la máscara se mantuvo aún con dosis altas de radiación UVC [20,21], [28][29][30][31].…”
Section: Medidas Fotométricasunclassified
See 1 more Smart Citation